Alcohol reduces muscle fatigue through atomistic interactions with nicotinic receptors - Noori, Hamid Reza; Vengeliene, Valentina; Schönig, Kai; Takahashi, Tatiane T.; Mosqueira, Matias; Bartsch, Dusan; Fink, Rainer; Spanagel, Rainer (Communications biology, 2018)
Hamid Noori et al. show that ethanol reduces muscle fatigue through its interaction with a negatively charged residue on the extracellular side of the nicotinic acetylcholine receptor. This work provides molecular insights on the ethanol effects on the peripheral nervous system.
Gesehen am 21.04.2020